EKSPLORASI MEDIA AUDIO VISUAL GURU PAI DALAM PEMBELAJARAN PAI DI SMP NEGERI 3 JOMBANG - Rifa'i, Alfa Alfi Adhumala; Arini, Aida (Rabbani: Jurnal Pendidikan Agama Islam, 2024)
ABSTRACT The existence of media in learning activities is quite important because as an intermediary the teacher communicates with his students, but its implementation must be consistent with the teaching materials so that the delivery can run optimally. Using a case study type of research with a qualitative approach where data is obtained from interviews, observation and documentation. Based on research, PAI learning at SMP Negeri 3 Jombang runs smoothly, students' grades are good and implementation of religious programs is consistent. Exploration of audio-visual media in PAI learning is constrained by learning facilities, the need to develop material visualization, and adjustments to students' learning characteristics. The dynamics of interaction between PAI teachers and students in using audio-visual media can be used as an evaluation of PAI learning and the relationship between PAI teachers and students can be established well, supported by the teacher's competence.